Sovereign credit risk, liquidity, and ECB intervention: Deus ex machina? - Loriana Pelizzon; Marti G. Subrahmanyam; Davide Tomio; Jun Uno (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
This paper examines the dynamic relationship between credit risk and liquidity in the sovereign bond market in the context of the European Central Bank (ECB) interventions. Using a comprehensive set of liquidity measures obtained from a detailed, quote-level dataset of the largest interdealer market for Italian government bonds, we show that changes in credit risk, as measured by the Italian sovereign credit default swap (CDS) spread, generally drive the liquidity of the market: a 10% change in the CDS spread leads a 11% change in the bid-ask spread. This relationship is stronger, and the transmission is faster, when the CDS spread is above the 500 basis point threshold, estimated endogenously, and can be ascribed to changes in margins and collateral, as well as clientele effects. Moreover, we show that the Long-Term Refinancing Operations (LTRO) intervention by the ECB weakened the sensitivity of the liquidity provision by the market makers to changes in the Italian government's credit risk. We also document the importance of market-wide and dealer-specific funding liquidity measures in determining the market liquidity for Italian government bonds.
Keywords: G01; G12; G14; 330; Liquidity; Credit Risk; Euro-zone Government Bonds; Financial Crisis; MTS Bond Market